A Longitudinal Analysis of the Effect of Mass Drug Administration on Acute Inflammatory Episodes and Disease Progression in Lymphedema Patients in Léogane, Haiti - Eddy, Brittany A. (The American Society of Tropical Medicine and Hygiene, 2014)
We conducted a longitudinal analysis of 117 lymphedema patients in a filariasis-endemic area of Haiti during 1995–2008. No difference in lymphedema progression between those who received or did not receive mass drug administration (MDA) was found on measures of foot (P = 0.24), ankle (P = 0.87), or leg (P = 0.46) circumference; leg volume displacement (P = 0.09), lymphedema stage (P = 0.93), or frequency of adenolymphangitis (ADL) episodes (P = 0.57). Rates of ADL per year were greater after initiation of MDA among both groups (P < 0.01). Nevertheless, patients who received MDA reported improvement in four areas of lymphedema-related quality of life (P ≤ 0.01). Decreases in foot and ankle circumference and ADL episodes were observed during the 1995-1998 lymphedema management study (P ≤ 0.01). This study represents the first longitudinal, quantitative, leg-specific analysis examining the clinical effect of diethylcarbamazine on lymphedema progression and ADL episodes.